2017
DOI: 10.1177/2050640617733922
|View full text |Cite
|
Sign up to set email alerts
|

A large proportion of fecal immunochemical test-positive participants in colorectal cancer screening is symptomatic

Abstract: BackgroundSymptomatic invitees are advised not to participate in colorectal cancer (CRC) screening but to directly consult their general practitioner (GP), because fecal immunochemical test (FIT) sensitivity for cancer is not optimal. This recommendation may not always be followed in daily practice. We evaluated how many FIT-positive participants had CRC-related symptoms and whether the presence of symptoms was associated with the presence and location of CRC/advanced neoplasia.MethodsWe prospectively collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…This implies that almost one out of five not detected with CRC would report rectal bleeding, while still only every fourth case of CRC would be identified by a history of rectal bleeding. A similar association between change in bowel habit and rectal bleeding with CRC was observed in the Dutch screening programme 18 while no association was found between symptoms and findings in the English and Scottish guaiac based FOBT screening programme. [19][20][21] Better sensitivity and specificity of FIT compared with guaiac based FOBT may be one reason for this difference.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…This implies that almost one out of five not detected with CRC would report rectal bleeding, while still only every fourth case of CRC would be identified by a history of rectal bleeding. A similar association between change in bowel habit and rectal bleeding with CRC was observed in the Dutch screening programme 18 while no association was found between symptoms and findings in the English and Scottish guaiac based FOBT screening programme. [19][20][21] Better sensitivity and specificity of FIT compared with guaiac based FOBT may be one reason for this difference.…”
Section: Discussionsupporting
confidence: 65%
“…In FOBT screening populations, the association between bowel symptoms and the detection of CRC or advanced adenomas is conflicting. [17][18][19][20][21] In FIT positive attenders, change in bowel habits had the strongest association with detection of CRC. However, the sensitivity was low, indicating that only a minority of individuals with CRC would be identified by change in bowel habits.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies have suggested that large proportions of colorectal cancer screening participants have underlying symptoms [26][27][28] despite recommendations and campaigns for symptomatic individuals to visit their GP. Some of these symptoms can be considered 'low risk, but not no risk' [29] and are often self-limiting but in combination can indicate underlying disease [13,14].…”
Section: Predictorsmentioning
confidence: 99%